MAXIMUM SUSTAINABLE YIELD (MSY) ESTIMATION AND CATCH POTENTIAL OF JINGA SHRIMP (Metapenaeus monoceros) IN WEST TANJUNG JABUNG WATERS, JAMBI PROVINCE - Yunita, Lauura Hermala; Saputri, Diah Maulani; Wulanda, Yoppie; Hariski, M; Wulandari, Wulandari; Hasanah, Hasanah (Asian Journal of Aquatic Sciences, 2025)
One of the key commodities in the capture fisheries sector is the Jinga Shrimp (Metapenaeus monoceros), which is widely distributed in tropical waters, including the coastal area of Tanjung Jabung Barat, Jambi Province. This study aims to estimate the Maximum Sustainable Yield (MSY) and the fishing potential of Jinga Shrimp in the waters of Tanjung Jabung Barat. The data used are secondary data on annual catch and fishing effort from 2017 to 2023, obtained from the local Fisheries Office. The analysis was conducted using the Schaefer model approach, which includes calculations of Catch per Unit Effort (CPUE), MSY, optimum effort (EMSY), Allowable Catch, utilization rate, and exploitation rate. The results showed an MSY value of 2,189.60 tons/year and an EMSY of 68.19 trips/year. As the safe harvest limit, the allowable catch was set at 1,751.68 tons/year (80% of MSY). The average utilization rate was 88%, indicating that the resource has not yet experienced overfishing. However, the exploitation rate has exceeded the optimum limit (124%) and is considered overfishing. The negative relationship between CPUE and effort (R² = 96.72%) indicates a decline in stock due to high fishing intensity. Therefore, adaptive and stock-based management policies are necessary to ensure this region's sustainable conservation of Jinga Shrimp populations.